2023
DOI: 10.3390/su15054016
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Initiatives, Education and Culture: Hubs for Enterprise Innovations and Economic Development

Abstract: The purpose of this research was to investigate the effects of entrepreneurial initiatives, entrepreneurial education, and entrepreneurial culture on enterprise innovation and economic development. The research was driven by the fact that entrepreneurship is a remarkable force which drives the enterprise growth, societal development, and economic development of a nation. The research adopted the social exchange theory and the economic theory as the basis of the literature. Primary data were used, collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
6
0
5
Order By: Relevance
“…Besides that, Ruiz et al [97] illustrated that CUL promotes personal entrepreneurial characteristics and traits, and related and risk-taking, adaptive strategies, which are important for new ventures' establishment, INO, and growth. Zemlyak et al [98] demonstrated that CUL, which is rooted in the societal context where businesses operate, positively influences INO because it helps new ventures to innovate, seek, and employ novel notions, and create a longstanding and sustainable competitive position. Thus, we provide the subsequent hypothesis: H2.…”
Section: H1 Entrepreneurial Financial Support (H1a) and Entrepreneuri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, Ruiz et al [97] illustrated that CUL promotes personal entrepreneurial characteristics and traits, and related and risk-taking, adaptive strategies, which are important for new ventures' establishment, INO, and growth. Zemlyak et al [98] demonstrated that CUL, which is rooted in the societal context where businesses operate, positively influences INO because it helps new ventures to innovate, seek, and employ novel notions, and create a longstanding and sustainable competitive position. Thus, we provide the subsequent hypothesis: H2.…”
Section: H1 Entrepreneurial Financial Support (H1a) and Entrepreneuri...mentioning
confidence: 99%
“…CUL also helps new ventures to develop INO by creating a climate which supports entrepreneurial activities, stimulating risk-taking activities to converse new concepts into actual productions and services [146], and thus INO can promote BuSuc since it helps firms to create more value from novel notions, skills, information, and approaches [107]. CUL positively affects new ventures' INO since it assists them in innovative processes and new idea employment [98], ultimately facilitating superior BuSuc by enforcing an innovative strategy [40]. Zemlyak et al [98] suggested that CUL is the ways of thinking and procedures of employing opportunities to establish new firms, products, and services, which stimulate the transformation and improvement of extant firms, new venture establishment, and their performance by developing innovative business procedures, boosting effectiveness, and assuring quality control.…”
Section: Mediating Functions Of Organizational Creativity and Firm In...mentioning
confidence: 99%
“…Для этого может потребоваться изменение законодательства и повышение ответственности за нарушения. Кроме того, важным шагом может стать улучшение конкуренции на рынке труда и введение механизмов защиты прав работников, например, создание профсоюзов [5,6,8].…”
Section: результаты исследования и их обсуждениеunclassified
“…However, it is recognized that education is not the sole factor influencing someone's readiness to engage in entrepreneurial activities (Wasim et al, 2024). Additional factors, such as local culture that promotes innovation, a business environment supportive of small and medium enterprises' growth, and the existence of policies facilitating business development, also have undeniable influence in facilitating the role of entrepreneurship in a country's economic dynamics (Zemlyak et al, 2023). Therefore, a deeper understanding of the complexity of interactions among these factors is crucial in designing sustainable education strategies and policies to support entrepreneurial development and create a conducive environment for innovation and inclusive economic growth.…”
Section: Introductionmentioning
confidence: 99%